Sosialisasi Pembuatan Wedang Pokak Untuk Meningkatkan Imunitas di Tengah Pandemi COVID-19 di Kelurahan Peneleh Kota Surabaya - Heidy Arviani; Rohmatul Afrida Nor Laili; Septiana Dina Mahiro (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The city of Surabaya is one of the cities in East Java with very high positive cases of COVID-19. Apart from adhering to health protocols, COVID-19 can be cured by itself or a self-limiting disease. Having a strong immune system is a way to fight viruses. Family Medicinal Plants (TOGA) are used to increase body immunity as a preventive measure to avoid contracting COVID-19. This community service activity was carried out in Peneleh Village, Genteng District, Surabaya City with one of its work programs being the socialization of making wedang pokak and distributing wedang pokak to the community. The outputs resulting from this activity include; (1) there is a video tutorial for making wedang pokak uploaded on the youtube channel